Thirty contaminants of emerging concern identified in secondary treated hospital wastewater and their removal by solar Fenton (like) and sulphate radicals-based advanced oxidation processes. Issue 6 (December 2021) - Lofrano, G.; Faiella, M.; Carotenuto, M.; Murgolo, S.; Mascolo, G.; Pucci, L.; Rizzo, L.
Abstract: Thirty contaminants of emerging concern (CECs) were identified and quantified in hospital wastewater (HWW) by LC-MS and their removal by solar photo Fenton (SPF) with ethylenediamine-N, N'-disuccinic acid (EDDS) at spontaneous pH (7.5) was compared to other solar driven advanced oxidation processes (AOPs) (namely, sunlight/persoxydisulphate (SPD) and sunlight/H2 O2 (SHP)). Almost all the detected CECs (28) are pharmaceuticals and belong to 13 different classes, with concentrations varied between 0.08 µg/L (psychiatric drug) to 38.92 µg/L (antidiabetic). First, the formation of iron-EDDS complexes was characterized by electrochemical methods to compare Fe 2+ and Fe 3+ behavior. The effect on a carbamazepine (CBZ) aqueous solution of solar driven Fe 2+ /EDDS and Fe 3+ /EDDS Fenton processes was comparatively evaluated to select the most effective one for advanced oxidation tests on real HWW and sunlight/Fe 2+ -EDDS/H2 O2 was the most effective one with 48% removal after 12.5 kJ/L -1 (78% total removal, 30% being under dark Fenton condition). SPF process was also more effective than SPD and SHP (60 min sunlight exposure, 5 kJ/L -1 ). Subsequently, the effect of the solar AOPs (SPF, Fe 2+ 0.1 mM, EDDS 0.2 Mm, H2 O2 2.7 Mm; SPD, PD 1.48 mM; SHP, H2 O2 2.7 Mm; 60 min sunlight exposure) was investigated in the treatment of the HWW and SPF resulted the most effective one, all CECs being removed from 70% to 100%. Graphical Abstract: ga1 Highlights: 28 out of 30 CECs identified as pharmaceuticals from 13 different classes. Concentrations between 80 ng/L (psychiatric drug) and 40 µg/L (antidiabetic) detected. Sunlight/Fe 2+ /EDDS (SPF) was more effective than sunlight/Fe 3+ /EDDS. SPF was the most effective AOP in the removal of CECs from hospital wastewater. CECs removals by SPF varied from 70% to 100%.